2014
DOI: 10.1007/s12070-014-0720-8
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Olfactory Dysfunction in Turkish Population with using Survey Method and Validated Olfactory Testing

Abstract: The aim of this study was to evaluate the effect of olfactory dysfunction on quality of life (QOL), and to investigate olfactory dysfunction related self-reported clinical features in Turkish population. The participants were questioned about the presence of any olfactory dysfunction. Participants with a complaint of olfactory dysfunction were asked to fill out a survey and then a validated olfactory test was performed. We asked 2,824 volunteers whether they had olfactory dysfunctions or not. A total of 199 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…The healthy volunteers also underwent Multi-Clinic Smell and Taste Questionnaire for study participation. This led to the fact that the incidence of olfactory disorder was found higher in our study compared to a study in the Turkish population using questionnaires 43 (57% vs 6.7%), possibly due to objective assessment with a standardized test tool. We also detected hyposmia in 29.8% of controls.…”
Section: Discussioncontrasting
confidence: 77%
“…The healthy volunteers also underwent Multi-Clinic Smell and Taste Questionnaire for study participation. This led to the fact that the incidence of olfactory disorder was found higher in our study compared to a study in the Turkish population using questionnaires 43 (57% vs 6.7%), possibly due to objective assessment with a standardized test tool. We also detected hyposmia in 29.8% of controls.…”
Section: Discussioncontrasting
confidence: 77%
“…Many studies have explored the QOL impact of OD. Those including safety-related issues have indicated increased incidence of fear or concern for gas leaks (49%-60% 67,68,76,77 ), smoke/fires (30%-50% 68,[77][78][79][80] ), chemical exposures (6%-40% 68,80 ), and eating spoiled foods (15%-71% 67,[76][77][78][79][80] ). However, only two of these studies employed some form of olfactory-intact control population, with one relying on patient-report of function, 68 and the other using objective testing.…”
Section: B Safetymentioning
confidence: 99%
“…Although, a detailed history was taken and an otorhinolaryngological examination was performed, we did not use another olfactory testing battery or electrophysiological testing, e.g., olfactometry, to confirm our results, although, there was a significant correlation between self-reporting olfactory dysfunction and olfactory tests. 3,25,26 Also, it was reported that, although the sensitivity of selfreporting olfactory dysfunction (ability of self-reporting to identify subjects truly with impairment) is poor (20%), the specificity (ability of self-reporting to identify subjects with normal olfactory function) is very high (94%). So, results of this study indicate that individuals with normal olfactory function tend to accurately report no abnormity.…”
Section: Discussionmentioning
confidence: 99%
“…Problems in quality of life are reported particularly in the areas of eating and safety, but olfaction also influences social communication, even reproductive behavior. [1][2][3][4][5][6] The major causes of olfactory disorders are infections of the upper respiratory tract, sinonasal diseases, head trauma, and toxic exposure. 7,8 Although, the prevalence of self-reported olfactory dysfunction was between 1.4% and 15%, population-based studies found the prevalence of olfactory dysfunction to be as high as 24%.…”
mentioning
confidence: 99%
See 1 more Smart Citation